Applied modelling of semiosphere in interspecific cohabitation contexts. - Delahaye, Pauline (Sign Systems Studies, 2024)
The semiosphere, as theorized by Jesper Hoffmeyer, is an interesting concept for those who want to create tools and models that need to consider a large variety of umwelten interacting and coexisting in the same space. As our contemporary times are witnessing a significant drop in biodiversity, and facing several issues that threaten both our ecosystems as well as human ways of living, the question arises what applications we can really obtain from these tools and models and how they can serve the purposes of sustainability, biodiversity conservation, environmental protection or cohabitation improvement. In this paper, I mainly explore the applications regarding the last-mentioned aspect, and also explain how it impacts the previous ones. I discuss the concept of interspecific cohabitation, listing the different categories of situations that can be included under this common denominator, and detail why this concept is central to understanding and apprehending the contemporary challenges we are facing. The article also observes the kinds of solutions that semiotics, via umwelt perspectives, can offer to improve this cohabitation or solve the issues interspecific contexts can generate.